Enabling New Mobile Applications with Location Proofs - Saroiu, Stefan; Wolman, Alec (Proceedings of the 10th International Workshop on Mobile Computing Systems and Applications (HotMobile), 2009)
Location is rapidly becoming the next “killer application” as location-enabled mobile handheld devices proliferate. One class of applications that has yet-to-emerge are those in which users have an incentive to lie about their location. These applications cannot rely solely on the users’ devices to discover and transmit location information because users have an incentive to cheat. Instead, such applications require their users to prove their locations. Unfortunately, today’s mobile users lack a mechanism to prove their current or past locations. Consequently, these applications have yet to take off despite their potential. This paper presents location proofs – a simple mechanism that enables the emergence of mobile applications that require “proof” of a user’s location. A location proof is a piece of data that certiﬁes a receiver to a geographical location. Location proofs are handed out by the wireless infrastructure (e.g., a Wi-Fi access point or a cell tower) to mobile devices. The relatively short range of the wireless radios ensures that these devices are in physical proximity to the wireless transmitter. As a result, these devices are capable of proving their current or past locations to mobile applications. In this paper, we start by describing a mechanism to implement location proofs. We then present a set of six future applications that require location proofs to enable their core functionality.